Graphene nanofilm as pressure and force sensor: A mechanical analysis. Issue 10 (9th October 2013) - Kam, K.; Scarpa, F.; Adhikari, S.; Chowdhury, R.
<x xml:space="preserve">Abstract</x> The out‐of‐plane mechanical bending properties of single layer graphene sheets (SLGS) are modelled using a molecular mechanics approach based on an atomistic–finite element formulation. Force/displacement curves for different rectangular SLGS with different aspect ratios are obtained for distributed (uniform pressure) and concentrated central loadings. We show that membrane and bending deformations scale differently based on the type of load, as well as geometry of the graphene sensor films.